PENINGKATAN JUMLAH PENJUALAN SAPI POTONG BERBASIS TEKNOLOGI MELALUI E-COMMERCE DI DESA SAMBI, KABUPATEN BOYOLALI - Fahman Hadi Utomo (Universitas 'Aisyiyah Surakarta, 2021)
This community service activity was carried out on Monday 5 April 2021. The implementation of service on increasing beef cattle sales with E-commerce involved one partner, namely the IZZAH SEJAHTERA MULTIFARM livestock farmer group, a beef cattle farm located in Ringinwok RT03/RW01, Jagoan Village, District Sambi, Boyolali Regency, Central Java with a population of 19 beef cattle. This beef cattle business is managed by a manager, Mr. Sulistyo, ST who is also the owner of the livestock business and two employees. The activities carried out include, Introduction and socialization about sales using the Facebook social media marketplace, Conducting training on how to make sales using the Facebook social media marketplace. Participants in community service activities were very enthusiastic about participating in the activity from beginning to end, even though in this activity they used e-meeting because the situation and conditions were still in the Covid-19 pandemic. Participants in the training on creating a Facebook marketplace account are very interested because so far partners are still using conventional marketing Keywords: Pelatihan; Pendampingan; Pemasaran.